Barreiras e facilitadores para a implantação da gestão por processos – um estudo em uma secretaria estadual de saúde - Alves, Anderson Alberto Gonçalves (2021)
The Brazilian public organizations often present opportunity of improvement in their work processes. There are notoriously noticeable gaps perceived by the citizens, who demand improvements in a progressive way. With its traditional and conservative characteristics, and presenting solid hierarchies and political transitions, these organizational structures present difficulties in applying established management models already estabilished in the private sector. The private organizations, in turn, became reference in terms of management practices for the public sector. In this time, comes the opportunity of success in management solutions through process management, also known as Business Process Management (BPM). In the area of the State Department of Health - SES/RS, numerous opportunities for improvement in work processes are perceived, especially related to communication, standardization and progress of processes. The process management, in turn, presents as main characteristics the management and controls of processes, by means of a systemic vision of the institution, aiming to equalize the performance of all the organizational processes. Starting from the perception of the lack of a management system for the process of work in the government organization studied, the necessity of this study is identified through the technique of process management, which through recent studies, presents improvements in work processes, seeking efficiency and effectiveness in private organizations.. As the main objective, this work seeked to analyze the barriers and facilitators for the implementation of process management in a state administrative unit of health, aiming to identify the main facilities and difficulties for the implementation of the aforementioned management model, as well as providing better management practices. This work is justified, starting from the identification of the problem, from the professional experience, apart from the concerns provided with the acquired knowledge during the academic experience, qualification and training. The approach of the research was qualitative and its objectives were in an exploratory way. The method used was through case study. The target audience of the present research were some servers of SES/RS. The data collection, happened through semi-structured interviews. The data analysis was executed from the data obtained from the interviews. The script of the interviews presented its questions divided into two different organizational environments, internal and external. The results showed positive aspects about the processes of work in the studied organization, much due to the technological evolution motivated by work in the home office regime facing a pandemic caused by coronavirus (COVID-19). On the other hand, there were some evident opportunities for improvement for the implementation of management processes in the organization focused on this study, especially an administrative reform aimed at technological innovation, in addition of awareness and collective spirit for the continuity of ongoing actions, improving, in that way, the public interest.